The Role of Digital Human Capital and Intellectual Capital in Strengthening Public Governance and Financial Accountability - Rabiyatul Jasiyah; Suriadi Suriadi; Husnah Katjina (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid advancement of digital technologies and the growing demand for public accountability have positioned digital human capital and intellectual capital as critical drivers of strengthening local government governance. This study examines the role of digital human capital and intellectual capital in enhancing public governance and sustainable regional financial performance accountability. This study employs a qualitative approach through a systematic literature review, drawing on peer-reviewed articles, government reports, and case studies published between 2010 and 2023. The findings show that digital human capital improves public service delivery and citizen engagement, while intellectual capital, comprising human, structural, and relational capital, enhances resource management and governance processes. The review also identifies challenges such as the digital divide and resistance to change that hinder the effective integration of these forms of capital. The paper suggests that integrating digital and intellectual capital can significantly improve financial accountability and governance outcomes, particularly in developing countries, where challenges to digital transformation are prevalent. However, further empirical studies are needed to explore the long-term impact and practical application of these resources in local government settings.